Individual and combinatorial effects of SNP and NaHS on morpho-physio-biochemical attributes and phytoextraction of chromium through Cr-stressed spinach (Spinacia oleracea L.) - Ma, Jing; Saleem, Muhammad Hamzah; Yasin, Ghulam; Mumtaz, Sahar; Qureshi, Freeha Fatima; Ali, Baber; Ercisli, Sezai; Alhag, Sadeq K.; Ahmed, Ahmed Ezzat; Vodnar, Dan C.; Hussain, Iqbal; Marc, Romina Alina; et al. (Frontiers in Plant Science, 2022)
Soil contamination stimulated by metal stress is becoming a major issue now a days because it’s polluting our ecosystem. Elevated levels of chromium (Cr) in agricultural lands hinder the yield of food crops and impart detrimental impacts on physio-biochemical processes of plants. In this research, impact of two different levels of Cr (0 (no Cr), 150 and 300 µM on growth, biomass, photosynthetic activities, nutrients uptake, synthesis of ROS, concentration of various antioxidants, exclusion of organic acid and Cr bioaccumulation in different parts of the plants was investigated under exogenous treatment of individual and combinatorial application of sodium nitroprusside (SNP) (100 µM) and sodium hydrogen sulphide (NaHS) (600 µM) in spinach (Spinacia oleracea L.) plants. Our results illustrated that soil spiked with Cr reduced significantly (P ≤ 0.001) the growth, chlorophyll contents, gas exchange parameters and assimilation of essential nutrients in S. oleracea in comparison to soil which was not added with Cr. However, Cr toxicity enhanced pointers of oxidative stress such as MDA, H2O2 and EL, organic acid exudation, enzymatic antioxidants like SOD, POD and CAT, non-enzymatic antioxidants such as phenolic, flavonoid, ascorbic acid and anthocyanin and Cr contents in roots and shoots of S. oleracea. Results also revealed that contents of proline, free amino acids, soluble and reducing sugars also enhanced in plants treated with Cr in comparison to those S. oleracea not added with Cr. Furthermore, results also showed that exogenous application of individual and combinatorial of SNP and NaHS contribute significantly in the alleviation of Cr toxicity in S. oleracea by reducing its concentration and decreased the values of bioaccumulation factor (BAF). So, SNP and NaHS can be applied to those agricultural fields which are facing heavy metal toxicity especially Cr.